Effect of Socio-Scientific Issues Based-Instruction on Critical And Creative Thinking Skills on The Topic of Environmental Change - Yakun Paristri; Slamet Suyanto (Universitas Negeri Yogyakarta, 2026)
This study aims to determine: 1) the influence of the Socio-scientific Issues (SSI) based-instruction on critical thinking skills of the students of SMAN 2 Bantul; and 2) the influence of the Socioscaintific Issues based learning on creative thinking skills of the students of SMAN 2 Bantul. SSI learning steps include problem analysis, clarification of science, refocus on socioscientific dilemmas, role playing tasks, and meta-reflective activities. The conflict raised was whether or not a shrimp pond was needed on the southern coast of Bantul Regency and was discussed in the topic of environmental change. This research was a quasi-experimental research type Nonequivalent control group design. The research sample was taken from 2 classes, one class as the experimental class and the other as the control class. The sampling technique used in this study was cluster random sampling. The data were collected using a written test, the observation sheet for the implementation of the learning model and the student response questionnaire. Data were analyzed using one-way ANOVA.The results of this study indicate that: 1). The SSI learning model in Biology learning has a very significant effect on the critical thinking skills of students of SMAN 2 Bantul with a significance value 0.00. This effect is on the aspects of providing simple explanations, developing basic skills, concluding, making further explanations and arranging strategies and tactics.; 2) The SSI learning model in Biology learning has a very significant effect on creative thinking skills in students of SMAN 2 Bantul with a significance value 0.00. This influence on the aspects of fluency, flexibility, originality and elaboration.